Development of a modified head and neck quality assurance phantom for use in stereotactic radiosurgery trials. (8th July 2013) - Faught, Austin M.; Kry, Stephen F.; Luo, Dershan; Molineu, Andrea; Bellezza, David; Gerber, Russell L.; Davidson, Scott E.; Bosch, Walter; Drzymala, Robert E.; Galvin, Jim; Timmerman, Robert; Sheehan, Jason; et al.
Abstract : An anthropomorphic head phantom, constructed from a water‐equivalent plastic shell with only a spherical target, was modified to include a nonspherical target (pituitary) and an adjacent organ at risk (OAR) (optic chiasm), within 2 mm, simulating the anatomy encountered when treating acromegaly. The target and OAR spatial proximity provided a more realistic treatment planning and dose delivery exercise. A separate dosimetry insert contained two TLD for absolute dosimetry and radiochromic film, in the sagittal and coronal planes, for relative dosimetry. The prescription was 25 Gy to 90% of the GTV, with ≤ 10 % of the OAR volume receiving ≥ 8 Gy for the phantom trial. The modified phantom was used to test the rigor of the treatment planning process and phantom reproducibility using a Gamma Knife, CyberKnife, and linear accelerator (linac)‐based radiosurgery system. Delivery reproducibility was tested by repeating each irradiation three times. TLD results from three irradiations on a CyberKnife and Gamma Knife agreed with the calculated target dose to within ± 4% with a maximum coefficient of variation of ± 2.1 % . Gamma analysis in the coronal and sagittal film planes showed an average passing rate of 99.4% and 99.5% using ± 5 % / 3 mm criteria, respectively. Results from the linac irradiation were within ± 6.2 % for TLD with a coefficient of variation of ± 0.1 % . Distance to agreement was calculated to be 1.2 mm and 1.3 mm along the inferior and superior edges of the target in the sagittal film plane, and 1.2 mm for both superior and inferior edges in the coronal film plane. A modified, anatomically realistic SRS phantom was developed that provided a realistic clinical planning and delivery challenge that can be used to credential institutions wanting to participate in NCI‐funded clinical trials. PACS number: 87.55 ‐v